Descriptive-analytic assessment of Manansala's linguistic performance in his 1964 autobiography - Jabal, Ronaldo Fidel (College of Arts and Letters, University of the Philippines Diliman, 1993)
The study titled Descriptive-Analytic Assessment of Manansala's Linguistic Performance in His 1964 Autobiography seeks to answer the question: Is the linguistic competence of a language user implied in his linguistic performance? It uses the 1964 Manansala autobiography published by Ambeth Ocampo in Sunday Inquirer Magazine. Finally, it forwards a humble alternative in the study of linguistic competence using Transformational-Generative Grammar by Noam Chomsky. The findings of the study are as follows: 1) Manansala's linguistic performance yielded his linguistic competence. 2) His sentences are comprehensible despite their ill-formedness. 3) He has more performance errors than competence errors. 4) Finally, Manansala's non-sentences are part his writing style.